A Correlation Between Differentiation Phenotypes of Infused T Cells and Anti-Cancer Immunotherapy - Ren, Hao; Cao, Kunkun; Wang, Mingjun (Frontiers in Immunology, 2021)
T-cell therapy, usually with ex-vivo expansion, is very promising to treat cancer. Differentiation status of infused T cells is a crucial parameter for their persistence and antitumor immunity. Key phenotypic molecules are effective and efficient to analyze differentiation status. Differentiation status is crucial for T cell exhaustion, in-vivo lifespan, antitumor immunity, and even antitumor pharmacological interventions. Strategies including cytokines, Akt, Wnt and Notch signaling, epigenetics, and metabolites have been developed to produce less differentiated T cells. Clinical trials have shown better clinical outcomes from infusion of T cells with less differentiated phenotypes. CD27+, CCR7+ and CD62L+ have been the most clinically relevant phenotypic molecules, while Tscm and Tcm the most clinically relevant subtypes. Currently, CD27+, CD62L+ and CCR7+ are recommended in the differentiation phenotype to evaluate strategies of enhancing stemness. Future studies may discover highly clinically relevant differentiation phenotypes for specific T-cell production methods or specific subtypes of cancer patients, with the advantages of precision medicine.